Urgensi Perencanaan Pendidikan Karakter pada Anak dalam Membentuk Kepribadian yang Baik: The Urgency of Character Education Planning for Children in Forming a Good Personality - Isroaini, Farida; Fahru Rozi; Ahmad Manshur; Zaini Miftah; Ida Fauziatun Nisa’ (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to describe how to plan character education for children in order to form a good personality in children. This research is literature-based with a desk research component. Data collection involves information from various literature sources, not only limited to books, but also including magazines, materials and other research. The main focus of desk research is to find various theories, laws, arguments, principles, opinions, ideas and other materials that can be used to examine and solve the problem under study. The conclusion of this research is that character education planning must be done immediately to foster the next generation of the nation. Through the use of these character-building elements, the goals of the national education system will be achieved.